Overview On Pakistan R&D Sector In Context Adopting Technological Capabilities - Asim, Zeeshan; Sorooshian, Shahryar (2017)
Potential information at current circumstances on R&D driven firms plays a crucial role to starch a rapid growth in most emerging and even in developing economies. Because of dynamic business environment it difficult to aligned nature of business with respect to either acquiring the technological capabilities. Pakistan is straggle in global business domain because of lack of understanding regarding to sustain the technological capabilities in order to boost domestic industries for economic stability. Number of studies predominantly explores the concept of technological capabilities in context of technology creation to technology acquisition. However, the establishment of technological capabilities always long term commitment. Based on the resource based-view theory this research article map the current R&D status of Pakistan with respects some of the emerging economies in context of sustaining the technological capabilities. Finally this paper will explores the information of potential limitations face by R&D sector in case of Pakistan.